A field test of unconventional camera trap distance sampling to estimate abundance of marmot populations. Issue 4 (8th October 2020) - Corlatti, Luca; Sivieri, Stefano; Sudolska, Bogna; Giacomelli, Stefano; Pedrotti, Luca
Abstract : The increasing use of remote motion‐sensitive photography recently led to an extension of distance sampling (DS) to accommodate camera trap data. Camera trap distance sampling (CTDS) has been proposed as a promising tool to estimate animal abundance, if temporally limited availability for detection is accounted for. However, the performance of CTDS in different field situations, and its reliability when single still images are used instead of videos or bursts of images remain untested. We used Alpine marmots Marmota marmota in the Stelvio National Park (Italy) to address three aims: 1) compare estimates of availability bias‐corrected CTDS when using single still images with different set‐ups to define sampling effort. For the 'user‐manual' set‐up we used values of θ [angle of view] and t ∗ [recovery time, i.e. the shortest interval at which an animal can be detected] specified by the camera user manual. For the 'empirical' set‐up we estimated θ and t ∗ empirically. 2) Compare estimates of CTDS and line DS, both corrected for availability bias based on marmot behavior. 3) Compare estimates of CTDS corrected for availability bias with estimates obtained with capture–mark–recapture (CMR), accounting for the effective trapped area. Our results suggest that: 1) CTDS with 'user‐manual' set‐up underestimated population size compared to the 'empirical' set‐up; 2) 'empirical' CTDS estimates were similar to those of line DS, but CTDS had lower precision; 3) availability bias‐corrected CTDS underestimated abundance compared to CMR. Assessing camera settings empirically is crucial to reduce bias in CTDS estimators when single still images are used. Videos should be preferred as they allow choosing predefined snapshot moments and do not rely on settings that cannot be changed. Overall, our results support the use of CTDS as an alternative to DS, although proper availability‐bias corrections and many cameras are needed to ensure accuracy and acceptable precision.